The effects of emerging environmental contaminants on Stenotrophomonas maltophilia isolated from drinking water in planktonic and sessile states - Gomes, Inês B. (2018)
Concerns on the presence of emerging contaminants (ECs) in water sources have increased in recent years. The lack of efficient technologies to remove ECs from residual waters contributes for their appearance in drinking water distribution systems (DWDS). Therefore, sessile microorganisms on DWDS pipes are continuously exposed to trace concentrations of ECs. However, no data exists on the role of ECs on the resident microbiota. The present work aims to understand the effects of prolonged exposure of a bacterial strain of Stenotrophomonas maltophilia, isolated from a DWDS, in both planktonic and biofilm states, to trace concentrations of selected ECs (antipyrineANTP; diclofenac sodium saltDCF; ibuprofenIBP; galaxolideGAL; tonalideTON; carbamazepineCBZ; clofibric acidCA; tylosinTY) on its tolerance to sodium hypochlorite (NaOCl) and resistance to antibiotics. Pre-established S. maltophilia biofilms were exposed to ECs for 26 d. Subsequently, the planktonic behaviour of the biofilm cells grown in the presence of ECS was characterized in terms of susceptibility to NaOCl and to selected antibiotics (levofloxacin and trimethoprim-sulfamethoxazole). Moreover, S.maltophilia was tested on its biofilm productivity in the presence of ECs (alone and mixed). These biofilms were challenged by NaOCl in order to assess the role of ECs on biofilm susceptibility. The results did not evidence remarkable effects of ECs on planktonic S. maltophilia susceptibility to NaOCl and antibiotics. However, S. maltophilia biofilm production and susceptibility to NaOCl was affected from ECs pre-exposure, particularly by the combination of different ECs (CA+CBZ, CA+IBP, CA+CBZ+IBP). S. maltophilia biofilms became more resistant to removal by NaOCl when developed in the presence of mixtures of CA+CBZ and CA+CBZ+IBP. Also, biofilm production was significantly affected. CA was present in all the combinations that altered biofilm behaviour. The overall results propose that exposure to ECs for 26days had not a huge impact on S. maltophilia planktonic antimicrobial susceptibility. Nevertheless, the prolonged exposure to some ECs altered biofilm production and tolerance to NaOCl, with a potential practical outcome of hindering DWDS disinfection. The simultaneous presence of different ECs in the environment may amplify biofilm resilience.